On Graphic Arts of the Early Romanian Books Printed in Brașov in Romanian Art History - Ana-Magdalena Petraru (Anastasis: Research in Medieval Culture and Art, 2022)
Book review: Anca Elisabeta Tatay, Cornel Tatai-Baltă, Arta grafică a cărților românești vechi tipărite la Brașov/ The Graphic Arts of the Early Romanian Books Printed in Brașov, Mega Publishing House, Cluj-Napoca, 2020, 241 pages